1989
DOI: 10.1128/jb.171.9.5229-5231.1989
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the pleiotropic phenotypes of rifampin-resistant rpoB mutants of Escherichia coli

Abstract: We used our collection of 17 sequenced rifampin resistance alleles in rpoB to perform a systematic analysis of the phenotypes historically reported with this class of mutants, including growth phenotype, ability to support the growth of different bacteriophages, ability to maintain the F' episome, interaction with mutant alleles at other loci, sensitivity to uracil, inhibition by 5-fluorouridine, and dominance. We found that mutational changes leading to the same phenotype were often located together and that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
121
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(130 citation statements)
references
References 19 publications
(17 reference statements)
9
121
0
Order By: Relevance
“…Overall, the nature of the defects of these mutant RNAPs interacting with these four stringent promoters is comparable, although the degree of the defect of each mutant RNAP at each promoter is not necessarily the same. Such a defect might be responsible for the slow-growth phenotypes of these rpoB mutants (9). At present, we do not know which step in initiation is defective at these promoters for the mutant RNAPs.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Overall, the nature of the defects of these mutant RNAPs interacting with these four stringent promoters is comparable, although the degree of the defect of each mutant RNAP at each promoter is not necessarily the same. Such a defect might be responsible for the slow-growth phenotypes of these rpoB mutants (9). At present, we do not know which step in initiation is defective at these promoters for the mutant RNAPs.…”
Section: Discussionmentioning
confidence: 90%
“…Recently, we found that four rpoB mutations [rpoB114(S531F), rpoB3449(⌬532A), rpoB3443(L533P), and rpoB3370(T563P)] (7), which are among previously characterized Rif r alleles (8,9), have specifically reduced the transcription from the two major promoters, P1 and P2, of the rpoD operon (10,11), leading to a hyper-temperature-sensitive phenotype of a 70 mutant (9). Because these two promoters are negatively controlled by the stringent response (12), it suggests that these rpoB mutants have specifically altered interaction with stringent promoters.…”
mentioning
confidence: 99%
“…kinetics | stringent response | transcription M utations to the primary RNAP genes in bacteria (rpoABCZ encoding the core α, β, β′, and ω subunits and rpoD encoding the housekeeping σ 70 subunit) exhibit a wide range of pleiotropic effects on bacterial phenotypes (1)(2)(3)(4)(5), and it has been said that mutations to RNAP genes can satisfy virtually any selection (6). We recently described the discovery of mutations in rpoB and rpoC following adaptive evolution of Escherichia coli K-12 MG1655 in glycerol M9 minimal medium (GMM) over a period of several weeks (7).…”
mentioning
confidence: 99%
“…At the same time, however, motility, flagellin production, growth rate, sensitivity towards certain phages and the virulence of Rif r mutant strains have been changed. Pleiotropic effect is often the result of rpoB mutation (Jin and Gross, 1989), which most frequently determines rifampicin resistance (Jin and Gross, 1988). Earlier Yamamori et al (1977) described nitrosoguanidine-induced Rif r mutation associated pleiotropic phenotypes in E. coli K-12.…”
Section: Genotypic Examinationsmentioning
confidence: 99%
“…In E. coli rifampicin resistance (Rif r ) is associated with specific nucleic acid substitutions in the gene encoding for RNA polymerase subunit β (rpoB) described by Jin and Gross (1988) and it has been found that rifampicin-resistant rpoB mutants cause pleiotropic phenotypes including growth phenotypes, ability to support different bacteriophages, ability to maintain the F' episome, interaction with mutant alleles at other loci, sensitivity to uracil, inhibition by 5-fluorouridine, and dominance recorded by Jin and Gross (1989). On the basis of these observations rifampicin-and ampicillin-resistant mutants were isolated and the motility, the production of FliC protein and flagella and the virulence of these antibiotic-resistant derivative strains were compared.…”
mentioning
confidence: 99%